2015
DOI: 10.1590/2175-7860201566317
|View full text |Cite
|
Sign up to set email alerts
|

Flora do Ceará, Brasil: Krameriaceae

Abstract: ResumoEste estudo consiste no levantamento florístico dos representantes de Krameriaceae no estado do Ceará, como parte do projeto "Flora do Ceará". O estudo foi baseado na análise comparativa dos caracteres morfológi-cos de espécimes depositados nos herbários EAC, HUEFS e UFRN, bibliografias especializadas, fotos de materiais-tipo, coletas e observações de campo. Foram registradas três espécies de Krameria: K. argentea, K. grandiflora e K. tomentosa. As espécies ocorrem preferencialmente em ambientes mais sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 85%
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 85%
“…O s m a p a s d e d i s t r i b u i ç ã o f o r a m confeccionados no programa DIVA-GIS 7.5 (Hijmans et al 2017) conforme as coordenadas disponíveis nas etiquetas de herbário; na ausência dessas informações, as coordenadas das localidades de coleta foram obtidas através da ferramenta GeoLoc (CRIA 2005). Para a organização do estudo, seguiu-se o padrão apresentado nas demais monografias sobre a flora do Ceará (e.g., Menezes et al 2013;Soares-Neto et al 2014a,b;Capistrano & Loiola 2015).…”
Section: Methodsunclassified
“…Despite previous efforts focused on Heliotropiaceae in Brazil, the representatives of this family in Ceará state are poorly studied, and the data regarding the family in the state is outdated. In this context, studies related to the "Flora of Ceará: knowing to conserve" project have shown how underestimated the floristic diversity of the state, particularly, due to new records (Capistrano & Loiola 2015;Tabosa et al 2016) and new species descriptions (Loiola 2013;Sampaio et al 2016Sampaio et al , 2019Souza et al 2016;Ribeiro et al 2017;Santos et al 2020) occurring frequently.…”
Section: Introductionmentioning
confidence: 99%